Sozio-kulturelle Kurzanalyse: Benin - Dirk Kohnert (Sozio-kulturelle Fragen in der Entwicklungspolitik II, 1995)
The process of democratic renewal that began in Benin in 1989 is considered a model for all of Africa. The sovereign national conference (February 1990), which was supported by all politically relevant forces, instituted a new civilian government. It created the conditions for the observance of essential human rights (release of all political prisoners, freedom of assembly, press and political parties, political neutrality of the army, etc.) and initiated economic liberalization. This effectively created better framework conditions for the development of democratic structures. The process of democratization in Benin was largely supported by the intellectual upper and middle classes of the urban centers. Beninese governance is not based on the balance of power of political associations and social groups, firmly anchored in the people, nor on a sense of national togetherness. Far more decisive are clientelism, regionalism, political ethnicity and competing customary systems of "traditional" rule. Most women are only marginally involved in political decision-making structures. Benin is one of the poorest countries in the world. Under the auspices of the "African Crisis", the African shadow economy has become a major means of securing survival across all strata of society. Even a job in the formal sector often serves only as a springboard for securing the earning potential in the informal sector. However, the parallel economy, such as gasoline and automobile smuggling between Benin and Nigeria, withdraws essential resources that the state would urgently need to develop the country. In urban regions, a layer of absentee landlords develops, accompanied by a pronounced socio-economic differentiation within the villages in large, medium and small farming families as well as day laborers and migrant workers. – – Der 1989 in Benin einsetzende demokratische Erneuerungsprozeß gilt als Modell für ganz Afrika. Die von allen politisch relevanten Kräften getragene souveräne Nationalkonferenz (Febr . 1990) setzte eine neue zivile Regierung ein. Sie schuf die Voraussetzungen für die Einhaltung wesentlicher Menschenrechte (Freilassung aller politischen Gefangenen, Versammlungs-, Presse- und Parteienfreiheit, politische Neutralität der Armee etc.) und leitete die Wirtschaftsliberalisierung ein. Somit wurden effektiv bessere Rahmenbedingungen für den Aufbau demokratischer Strukturen geschaffen. Der Demokratisierungsprozeß in Benin wurde wesentlich von der intellektuellen Ober- und Mittelschicht der urbanen Zentren getragen. Die Herrschaft der beninischen Staatsführung beruht nicht auf dem Machtgleichgewicht der im Volke fest verankerten politischen Verbände und gesellschaftlichen Gruppierungen oder auf einem Gefühl der nationalen Zusammengehörigkeit. Weitaus entscheidender sind nach wie vor Klientelismus, Regionalismus, politische Ethnizität und konkurrierende "traditionelle" Herrschaft-Systeme. Die meisten Frauen sind an den politischen Entscheidungsstrukturen nicht oder nur marginal beteiligt. Benin gehört zu den ärmsten Ländern der Welt. Unter dem Vorzeichen der "afrikanischen Krise" ist die afrikanische Schattenwirtschaf - alle Gesellschaftsschichten übergreifend - zu einem wesentlich en Mittel der Überlebenssicherung geworden. Selbst ein Arbeitsplatz im formellen Sektor dient oft nur als Sprungbrett für die Absicherung der Verdienstmöglichkeiten im informellen Sektor. Allerdings entzieht die Parallelwirtschaft , wie z.B. der Benzin- und KFZ-Schmuggel zwischen Benin und Nigeria, dem Staat wesentliche Ressourcen, die er dringend zur Entwicklung des Landes benötigt. Im Einzugsbereich der größeren Städte entwickelt sich eine Schicht von absentee landlords sowie eine ausgeprägte sozio-ökonomische Differenzierung innerhalb der Dörfer in Groß-, Mittel- und Kleinbauernfamilien sowie Tagelöhner oder Wanderarbeiter.
Additional information: Reprint in revised version of Dirk Kohnert: "Sozio-kulturelle Kurzanalyse: Benin", Africa Spectrum, Vol. 26, No. 3 (14 November 1991), pp. 405-414
Keywords: F54; N37; N47; Z13; 330; Benin; Sozialstruktur; Soziale Schichtung; Soziale Mobilität